Berbagai Imbangan Jerami Padi Dengan Kaliandra (Calliandra calothyrsus) Terfermentasi Terhadap Penampilan Fisik dan Nutrisi Silase - I Kadek Agus Wardana; Yan Tonga; I Gede Sutapa (GEMA AGRO, 2019)
The purpose of this study was to determine the balance of straw and calliandra fermented with physical quality and nutritional silage. This study was used as a Completely Randomized Design (CRD) with 6 treatments and 3 replications. R0 (control, rice straw not mixed with calliandra). R1 (mixing rice straw and calliandra with straw ratio of 90% and calliandra 10%), R2 (mixing rice straw and calliandra with a ratio of 80% straw and calliandra 20%), R3 (mixing rice straw and calliandra with a ratio of 70% straw and calliandra 30%), R4 (mixing straw and calliandra with straw ratio of 60% and calliandra 40%), R5 (mixing straw and calliandra with comparison straw 50% and calliandra 50%). Judging from the physical appearance for the (color, aroma, and texture) the parameters did not differ significantly between all treatments (P> 0.05). The best treatment is the treatment of R5 (rice straw ration and 50%: 50% calliandra). Judging from nutrient silage for water parameters and no dry matter and crude protein showed that the real effect was different from (P> 0.05) ash content, organic matter, and crude protein showed very significant effect (P <0.01). The highest yield of organic matter and crude protein is R5 (ratio of rice straw and kaliandra 50%: 50%) with the highest percentage of organic matter 81.63% and the highest crude protein 15.35%.